2021
DOI: 10.3390/biomedicines9111536
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Previa Complicated with Endometriosis: Contemporary Clinical Management, Molecular Mechanisms, and Future Research Opportunities

Abstract: Endometriosis is a common gynecological disease characterized by chronic inflammation, with an estimated prevalence of approximately 5–15% in reproductive-aged women. This study aimed to assess the relationship between placenta previa (PP) and endometriosis. We performed a systematic review of the literature until 30 June 2021, and 24 studies met the inclusion criteria. Using an adjusted pooled analysis, we found that women with endometriosis had a significantly increased rate of PP (adjusted odds ratio (OR) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 114 publications
(303 reference statements)
0
18
0
1
Order By: Relevance
“…The association between endometriosis and an increased risk of placenta previa is robust [ 23 , 24 , 29 , 97 , 98 ]. Notably, placenta previa is the most significant risk factor for PASD [ 15 , 17 , 98 , 99 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between endometriosis and an increased risk of placenta previa is robust [ 23 , 24 , 29 , 97 , 98 ]. Notably, placenta previa is the most significant risk factor for PASD [ 15 , 17 , 98 , 99 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since endometriotic lesions are difficult to diagnose in pregnant women, the current study identified endometriosis in pregnant women with the following criteria [ 29 ]: (i) histologically confirmed endometriosis; (ii) endometriosis diagnosed by clinical findings (e.g., ultrasound, pelvic adhesions, posterior uterine wall adhesions, or the existence of an endometriotic cyst); (iii) endometriosis suspected clinically or histopathologically during cesarean delivery; and (iv) women identified with endometriosis by using the International Classification of Diseases code. Severe endometriosis was defined as deep infiltrating endometriosis or revised American Society for Reproductive Medicine stage III or IV endometriosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since accurate diagnosis of endometriosis during pregnancy is challenging, endometriosis during pregnancy was defined in this study as previously described [ 21 ]: (i) a past surgical history for endometriosis; (ii) a clinical diagnosis of endometriosis (ultrasonographic findings, pelvic adhesions, PEUA, and ovarian endometrioma); (iii) a clinical or histopathological diagnosis of endometriosis during CD; and (iv) an International Classification of Diseases code registration for endometriosis.…”
Section: Methodsmentioning
confidence: 99%
“…In women with PAS, myometrial invasion interferes with placental detachment, leading to significant maternal morbidity [11][12][13][14][15]. Postpartum hemorrhage is a major complication of PAS, and intraoperative blood loss potentially exceeds several liters, possibly leading to shock and coagulopathy [16][17][18][19][20][21][22]. There is a risk of injury to surrounding organs with PAS, particularly to the bladder and ureter.…”
Section: Introductionmentioning
confidence: 99%